COLOR-INFORMATION TECHNOLOGIES AS A COMPONENT OF BRAND-COLORISTIC OF SEWING PRODUCTS - KULESHOVA, Svitlana; KOZAR, Oksana; MANDZYK, Igor (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article is devoted to solving the task of analyzing the essence, features, and rules of brand coloristic as a tool for influencing the target audience of a fashion brand. The authors proposed approaches to using mobile applications as color information technologies to develop brand coloristic of the projected image of a clothing model.As a result of the conducted research, a color design strategy for fashion brand garments was developed. The essence of a comprehensive study of color perception: its theory and practice, personalities, institutions, semantics, and the use of color information technologies for developing brand coloristic of the projected image of a clothing model is substantiated. The interaction of color in art, design, advertising, and science has been proven. Based on consumers' physiological, emotional, intellectual, and behavioral reactions to color, a comprehensive system, "The meaning of color," is proposed. The motives and behavioral mechanisms of consumers in the fashion industry have been studied, and the factors affecting the purchase decision have been determined. This made it possible to represent the information model of the reaction to the garment, as a component of the clothing color design strategy, by including subsets of stimuli and emotions in the design-projection process. The main rules of modern brand coloristic were analyzed and applied using modern color information technologies in the form of a ready-made Color Gear mobile application. The proposed process of using current color and information technologies to harmonize the graphic fashion image allows you to get an individual coordinated project image with a planned impression. Thus, it has been proven that the elements of brand color are an essential factor that affects the consumer's perception of fashion brands and, as a result, sales and profits. Broad prospects for further development of the author's mobile application for harmonizing clothing colors have been revealed, especially when it comes to finding a new color project image because the competition of fashion brands is active and demanding at the current stage.
Keywords: fashion brand; brand color; color perception; color information technology